2003
DOI: 10.1292/jvms.65.141
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Investigations of an Outbreak of Intestinal Atresia in Two Israeli Dairy Herds.

Abstract: ABSTRACT. An epidemiological investigation of an outbreak of intestinal atresia in Israeli Holstein-Friesian newborn calves showed a linkage with rectal palpation for early pregnancy diagnosis, performed less than 42 days after insemination. The odds of an exposed calf, i.e., one born to a dam that was diagnosed by early palpation as having intestinal atresia were 119.7 times higher than one bor n in normal control herds (95% CI; 7.4-1946.3). A total of 682 calves-at-risk was recorded from mid-1998 to mid-2000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
1
19
0
1
Order By: Relevance
“…The present investigation adds new information suggesting that ASP does not influence the calving rates and extending knowledge about the subject. It has been reported that early pregnancy diagnosis by ASP during the embryonic period (first 45 days of gestation) [30], especially between 36 and 42 days of gestation, was associated with an increased risk of atresia coli and/or jejuni [31][32][33][34][35]. In the United States, one calf was diagnosed with atresia coli from an investigation with the use of organic phosphate systemic insecticides pour-on [31]; however, these authors mentioned that this abnormality was previously noticed in eight calves from 798 neonatal necropsies covering 15 years from 1963 to 1977 in an experimental station in Montana [41].…”
Section: Groupmentioning
confidence: 99%
See 2 more Smart Citations
“…The present investigation adds new information suggesting that ASP does not influence the calving rates and extending knowledge about the subject. It has been reported that early pregnancy diagnosis by ASP during the embryonic period (first 45 days of gestation) [30], especially between 36 and 42 days of gestation, was associated with an increased risk of atresia coli and/or jejuni [31][32][33][34][35]. In the United States, one calf was diagnosed with atresia coli from an investigation with the use of organic phosphate systemic insecticides pour-on [31]; however, these authors mentioned that this abnormality was previously noticed in eight calves from 798 neonatal necropsies covering 15 years from 1963 to 1977 in an experimental station in Montana [41].…”
Section: Groupmentioning
confidence: 99%
“…However, in those studies, no information about calving rates or clinical abnormalities of the newborn calves was reported. Studies in the United States and in other areas of the world have observed an association between amniotic sac palpation (ASP) during the embryonic period for pregnancy diagnosis until Day 45 of gestation [30] and an increased risk of atresia coli and/or jejuni in newborn calves [31][32][33][34][35]. In atresia coli and/or jejuni, a section of the large bowel or jejuni is absent, resulting in a blind-ending intestinal tube.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although atresia ani is likely the most common intestinal atresia encountered, atresia coli and atresia jejuni are most represented in the scientific literature. 10 I have diagnosed atresia coli in a variety of beef breeds, including Charolais, Angus, Short Horn, and Polled Hereford. In one report, an incidence rate of 0.76% was reported in a university dairy herd of Holstein cows over a 10-year period.…”
mentioning
confidence: 99%
“…Vascular development and extensive spiraling of the colon occurs during organogenesis (days 12-45 of gestation) in the fetus. (Brenner and Orgad, 2003) noted when the early pregnancy diagnosis by amniotic vesicle palpation was applied; intestinal atresia was associated with it in a frequency-dependent manner.…”
Section: Resultsmentioning
confidence: 99%